Saavedra, Villa Ortúzar, Palermo, Spoon River: Borges’s translations of Edgar Lee Masters in Sur magazine - Deviagge, Zenón (Universidad Nacional del Litoral, 2019)
This article examines three poems of Edgar Lee Masters translated by Jorge Luis Borges in Sur magazine, in 1931. The research of specific conditions of a translation project developed in his early work allows us to consider those translations as a possible point of tension between a «criollista» Borges and his later «universal» turn.